2014
DOI: 10.1037/a0036438
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived racial discrimination predict changes in psychological distress and substance use over time? An examination among Black emerging adults.

Abstract: We assessed whether perceived discrimination predicted changes in psychological distress and substance use over time and whether psychological distress and substance use predicted change in perceived discrimination over time. We also assessed whether associations between these constructs varied by gender. Our sample included 607 Black emerging adults (53% female) followed for four years. Participants reported the frequency with which they had experienced racial hassles during the past year, symptoms of anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(129 citation statements)
references
References 52 publications
5
124
0
Order By: Relevance
“…Increases over time in retail outlet density and targeted advertising also could have contributed to the greater increases in consumption among Blacks, as various studies have shown that Blacks are disproportionately affected by these factors (Alaniz, 1998; Kwate and Lee, 2007; McKee et al, 2011; Theall et al, 2011); Although the change in oversampling procedures that permitted two respondents in selected minority households in the NESARC-III could play a role, the small extent to which it may have resulted in a greater proportion of Black respondents in areas of high minority concentration would not likely inflate increases in consumption among Blacks. Rather, studies have shown that living in areas with high minority concentrations is associated with lower consumption among Blacks, possibly because it reduces drinking related to the stresses of acculturation and perceived discrimination (Bécares et al, 2011; Hurd et al, 2014; Monshouwer et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Increases over time in retail outlet density and targeted advertising also could have contributed to the greater increases in consumption among Blacks, as various studies have shown that Blacks are disproportionately affected by these factors (Alaniz, 1998; Kwate and Lee, 2007; McKee et al, 2011; Theall et al, 2011); Although the change in oversampling procedures that permitted two respondents in selected minority households in the NESARC-III could play a role, the small extent to which it may have resulted in a greater proportion of Black respondents in areas of high minority concentration would not likely inflate increases in consumption among Blacks. Rather, studies have shown that living in areas with high minority concentrations is associated with lower consumption among Blacks, possibly because it reduces drinking related to the stresses of acculturation and perceived discrimination (Bécares et al, 2011; Hurd et al, 2014; Monshouwer et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Whereas both studies included neighborhood-quality variables in the measure of environmental harshness, the FACHS also used a measure of perceived racial discrimination and the three elements of environmental harshness (discrimination, parenting, and neighborhood) were not combined. For African-Americans, perceived racial discrimination is a powerful stressor related to negative outcomes including substance use and depression (e.g., Hurd, Varner, Caldwell, & Zimmerman, 2014). Despite the absence of measured racial discrimination in the present White sample, similar to the FACHS, a pathway from harsh environments to later adjustment through fast FHS was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Among Hispanic=Latino high school students, higher perceived discrimination has been found to longitudinally predict more tobacco, alcohol, and marijuana use, while stronger ethnic identity has been found to longitudinally predict less tobacco, alcohol, and marijuana use (Unger, Schwartz, Huh, Soto, & Baezconde-Garbanati, 2014). Studies conducted with other racial=ethnic minority adolescents (e.g., Asian Americans, Pacific Islanders, African Americans) have found racial discrimination to be positively associated with both mental health and substance use problems (Chen, Szalacha, & Menon, 2014;Hurd, Varner, Caldwell, & Zimmerman, 2014). …”
Section: Acculturative Stress=discrimination and Underage Drinkingmentioning
confidence: 98%